The Challenges of Knowledge Sharing Practices in Higher Educational Institutions in Namakkal District of Tamilnadu: A Kendall Approach - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
The present study has made an attempt to analyse the various challenges in knowledge sharing behaviour among the faculty members working in higher educational institutions in Namakkal district of Tamilnadu, India. The primary data were collected from the faculty members working in Arts and Science Colleges, Engineering Colleges, Standalone Institutions and Polytechnic Colleges in the district. The main objective of the objective of the study is to analyse the various challenges faced by the faculty members in knowledge sharing about their academic activities. Further, to analyse the relationship between demographic variables and challenges in knowledge sharing behaviour of faculty members in higher educational institutions. The statistical tool Kendall’s co-efficient concordance has been used to analyse the data. The Lack of time, Lack of rewards, Lack of interest, Fear of others performing better, Lack of availability of appropriate means and methods and Fear of losing importance are the important challenges in knowledge sharing in higher educational institutions. The management of higher educational institutions should take necessary steps to eradicate the various challenges in knowledge sharing and motivate the faculty members for effective collaborations and networking through knowledge sharing.